Size-dependent order-disorder crossover in hydrophobic hydration: comparison between spherical solutes and linear alcohols - Hande, Vrushali; Chakrabarty, Suman (ACS Omega, 2022)
Theory and computer simulation studies have predicted that water molecules around hydrophobic molecules should undergo an order-disorder transition with increasing solute size around a 1 nm length scale. Some theories predict the formation of a clathrate-like ordered structure around smaller hydrophobic solutes (<1 nm) and the formation of disordered vapor-liquid interfaces around larger solutes (>1 nm) and surfaces. Experimental validation of these predictions has often been elusive and contradictory. High-resolution Raman spectroscopy has detected that water around small hydrophobic solutes shows a signature similar to that of bulk water at lower temperature (increased ordering and a stronger hydrogen-bonded network). Similarly, water around larger solutes shows an increasing population of dangling OH bonds very similar to higher temperature bulk water. Thus, the solute size dependence of the structure and dynamics of water around hydrophobic molecules seems to have an analogy with the temperature dependence in bulk water. In this work, using atomistic classical molecular dynamics (MD) simulations, we have systematically investigated this aspect and characterized this interesting analogy. Structural order parameters including the tetrahedral order parameter (Q), hydrogen bond distribution, and vibrational power spectrum highlight this similarity. However, in contrast to the experimental observations, we do not observe any length-dependent crossover for linear hydrophobic alcohols (n-alkanols) using classical MD simulations. This is in agreement with earlier findings that linear alkane chains do not demonstrate the length-dependent order-disorder transition due to the presence of a sub-nanometer length scale along the cross section of the chain. Moreover, the collapsed state of linear hydrocarbon chains is not significantly populated for smaller chains (number of carbons below 20). In the context of our computational results, we raise several pertinent questions related to the sensitivity of various structural and dynamical parameters toward capturing these complex phenomena of hydrophobic hydration.